THE EFFECT OF INTEGRATING IOT SYSTEM IN THE SMART FARMING OF RED ONION (ALLIUM CEPA) - Chong Yu; Mimi Syazwani Suhaimi; Nurulakidah Adnan, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Smart farming is pivotal in advancing agriculture, offering innovative solutions to optimize crop yields and monitor plant growth. This study proposes the use of the Internet of Things (IoT) in smart farming to determine the optimal watering interval for red onions (Allium cepa). The system incorporates Arduino technology, utilizing a water pump and humidity sensor for automated irrigation. Three watering schedules were tested: 8, 12, and 18 hours. The results indicate that an 8-hour interval yielded the highest growth (3.5 ± 1.20 cm) within three weeks, followed by 12 hours (3.4 ± 1.33 cm) and 18 hours (2.0 ± 0.67 cm). Factors such as soil type, nutrition, and environmental conditions may influence these outcomes. Future work, including greenhouse cultivation, is suggested to enhance data precision and agricultural productivity.